THE DIALECTICS OF PRESERVATION AND RENEWAL IN TRADITIONAL DANCE: BEDHAYA SAPTONGKARA AS A DEVELOPMENT OF THE BEDHAYA GENRE - Syahrial, Syahrial; Sriyadi, S.; Wibowo, Angga Febri (Paradigma: Jurnal Kajian Budaya, 2026)
Bedhaya is a traditional Javanese court dance that embodies ethical, aesthetic, and sacred values. Following Indonesia’s independence, restrictions on its performance gradually eased, allowing the dance to be presented beyond the court and fostering its development within arts education. This shift generated a dialectic between cultural preservation and creative innovation, exemplified by Bedhaya Saptongkara, which integrates Balinese dance elements into the Javanese framework to produce an innovative form. Using a choreological approach and comparative method, this study reveals that although Bedhaya Saptongkara retains core principles of bedhaya, it does not fully adhere to the classical structure. Instead, it occupies the category of bedhayan, a derivative genre that reinterprets bedhaya principles within a new creative context. These findings affirm that tradition and innovation are not mutually exclusive; renewal can broaden cultural relevance while maintaining aesthetic roots